2017
DOI: 10.1186/s13024-017-0149-0
|View full text |Cite
|
Sign up to set email alerts
|

The SH-SY5Y cell line in Parkinson’s disease research: a systematic review

Abstract: Parkinson’s disease (PD) is a devastating and highly prevalent neurodegenerative disease for which only symptomatic treatment is available. In order to develop a truly effective disease-modifying therapy, improvement of our current understanding of the molecular and cellular mechanisms underlying PD pathogenesis and progression is crucial. For this purpose, standardization of research protocols and disease models is necessary. As human dopaminergic neurons, the cells mainly affected in PD, are difficult to obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
545
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 726 publications
(600 citation statements)
references
References 100 publications
(94 reference statements)
6
545
1
4
Order By: Relevance
“…The aim of this study is to obtain in-depth understanding of neurotoxicity of PQ by use of in vitro system. For this purpose, SH-SY5Y human neuroblastoma was selected because the cell is an established model to examine neurotoxicity of chemicals as well as stresses (Cheung et al, 2009;Xicoy et al, 2017) and is shown more sensitive to PQ toxicity than other cells (Zhao et al, 2017). We examined the possible involvement of recently discovered forms of cell death in SH-SY5Y human neuroblastoma cells during PQ exposure, as well as the involvement of other cell deathregulating mechanisms such as the mitochondrial damage response and autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study is to obtain in-depth understanding of neurotoxicity of PQ by use of in vitro system. For this purpose, SH-SY5Y human neuroblastoma was selected because the cell is an established model to examine neurotoxicity of chemicals as well as stresses (Cheung et al, 2009;Xicoy et al, 2017) and is shown more sensitive to PQ toxicity than other cells (Zhao et al, 2017). We examined the possible involvement of recently discovered forms of cell death in SH-SY5Y human neuroblastoma cells during PQ exposure, as well as the involvement of other cell deathregulating mechanisms such as the mitochondrial damage response and autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate whether miR-181a plays a role in these effects, we transfected SH-SY5Y cells, which are a well established model of human mDA neurons [18,38], with a miR-181a inhibitor/antagomir. Inhibition of miR-181a resulted in induction of Smad signalling and led to the promotion of neurite growth in these cells, in a similar fashion to that induced by the physiological ligand, GDF5, which was used as a positive control.…”
Section: Discussionmentioning
confidence: 99%
“…Having established the importance of the miR-181a targets genes, Smad1 and Smad5, in BMP/GDF ligand-induced neurite growth, we next determined whether miR-181a modulated Smad phosphorylation/activation and neurite growth in SH-SY5Y cells, which are a widely used cell line model of human mDA neurons which also express the miR181a targets, BMPR2 and Smad1/5 [18,38]. This cell line permits higher transfection efficiencies than primary neurons which facilitated molecular analysis [18].…”
Section: Mir-181a Inhibition Promotes Smad1/5 Phosphorylation and Neumentioning
confidence: 99%
“…[71][72][73] Due to their expression of dopaminergic markers, SH-SY5Y cells are used most frequently to model Parkinson's disease in vitro. A recent review of these studies demonstrates several such models, 74 where Parkinson's disease is simulated in a number of ways. One method involves over expressing α-synuclein (or the A53T/A30P mutants), 75,76 to varying success.…”
Section: Sh-sy5y Human Neuroblastoma Cell Linementioning
confidence: 99%